CD147 and MCT1-potential partners in bladder cancer aggressiveness and cisplatin resistance - Afonso, Julieta; Santos, Lucio L.; Miranda-Goncalves, Vera; Morais, Antonio; Amaro, Teresina; Longatto-Filho, Adhemar [UNESP]; Baltazar, Fatima (Wiley-Blackwell, 2015)
The relapsing and progressive nature of bladder tumors, and the heterogeneity in the response to cisplatin-containing regimens, are the major concerns in the care of urothelial bladder carcinoma (UBC) patients. The metabolic adaptations that alter the tumor microenvironment and thus contribute to chemoresistance have been poorly explored in UBC setting. We found significant associations between the immunoexpressions of the microenvironment-related molecules CD147, monocarboxylate transporters (MCTs) 1 and 4, CD44 and CAIX in tumor tissue sections from 114 UBC patients. The presence of MCT1 and/or MCT4 expressions was significantly associated with unfavorable clinicopathological parameters. The incidence of CD147 positive staining significantly increased with advancing stage, grade and type of lesion, and occurrence of lymphovascular invasion. Similar associations were observed when considering the concurrent expression of CD147 and MCT1. This expression profile lowered significantly the 5-year disease-free and overall survival rates. Moreover, when selecting patients who received platinum-based chemotherapy, the prognosis was significantly worse for those with MCT1 and CD147 positive tumors. CD147 specific silencing by small interfering RNAs (siRNAs) in UBC cells was accompanied by a decrease in MCT1 and MCT4 expressions and, importantly, an increase in chemosensitivity to cisplatin. Our results provide novel insights for the involvement of CD147 and MCTs in bladder cancer progression and resistance to cisplatin-based chemotherapy. We consider that the possible cooperative role of CD147 and MCT1 in determining cisplatin resistance should be further explored as a potential theranostics biomarker. (c) 2014 Wiley Periodicals, Inc.
Keywords: CD147; chemoresistance; monocarboxylate transporters; tumor microenvironment; urothelial bladder cancer